Religious Privatization in the UDI Community: Implications for Contemporary Islamic Education - Nasruddin Nasruddin; Moh. Kusno; Ghozi Ghozi (At- Ta'lim : Jurnal Pendidikan, 2026)
Religious privatization is a key phenomenon in contemporary transformations of religious authority, marked by epistemic fragmentation and growing exclusivism in Islamic knowledge production. It reshapes community relations and redefines boundaries between formal and non-formal Islamic education, with implications for national education policy, curriculum integration, and socio-religious polarization. The UDI community represents a critical case through closed religious spaces and an internally governed educational system autonomous from mainstream institutions such as madrasahs, pesantren, and universities. This study examines the production and reproduction of religious privatization in the UDI community and its implications for Islamic education. It employs a qualitative exploratory case study design, based on in-depth interviews with 20 key informants and participant observation in Kampung Baru, Lamongan, Indonesia. Data analysis follows an abductive approach integrating perspectives on religious privatization, authority, boundary-making, and critical Islamic education. Findings identify eight mechanisms producing a closed knowledge regime, centralized authority, and restricted epistemic access, generating a homogeneous, inward-looking educational model and contributing to fragmentation, institutional delegitimization, and polarization risks. The study reconceptualizes religious privatization beyond decentralization, arguing it is a productive institutional mechanism that generates, stabilizes, and normalizes epistemic boundaries restructuring relations among authority, knowledge, and Islamic education.